Improving Learning Outcomes of The Qur’an Hadits With STAD Model Cooperative Learning Method - Muhana Abu (International Journal of Management and Education in Human Development, 2023)
Purpose this study to Improve Activity and Achievement of Mathematics Subjects in Subject Number Material with Cooperative Learning Model of STAD. Type Place study is place used in do study for get the desired data. Study This located at MtsN 02 Kendari Research time is time ongoing study or moment study This took place. Study This held in month February semester even odd Year 2022. Subject study is students Class VII 2 MtsN 02 Kendari. Based on the existing deficiencies and student achievement in cycle I which did not meet the standards of success, this research was continued in cycle II. The results showed that the learning activities were in line with expectations. Weaknesses in cycle I have been overcome in cycle II so that all students have achieved learning mastery standards. Teacher activity in cooperative learning STAD model in learning Al-Qur'an Hadith is obtained at the first meeting of teacher activity using cooperative learning STAD model in learning with a score of 65 or on, the sufficient category and in the second meeting a score of 70 or good category is obtained and the overall average obtained 67.5 or sufficient category. Furthermore, student activities using the STAD cooperative learning model in learning the Qur'an Hadith in the first meeting were at a score of 53.93 or the sufficient category and the second meeting was obtained 64.48 or the sufficient category and the overall average was obtained 59.21 or the sufficient category. Student learning outcomes obtained an average value of students' Al-Qur'an Hadith learning achievement is 65.58. Students who complete their studies are 20 people or 64.67% and students who do not complete their learning outcomes are 14 people or 35.32%. These results indicate that in the first cycle classically students have not finished studying. Teacher activity in cycle II at the first meeting the teacher's activity using learning using the STAD Cooperative learning model in Al-Qur'an Hadith learning obtained a score of 80 or a good category and at the second meeting a score of 90 or a very good category was obtained and the overall average was obtained 85 or good category. At the first meeting it was at a score of 76.98 or the good and category. meeting H obtained 88.89% or very good category and the overall average was obtained 82.14 or good category. Student learning outcomes in cycle II obtained an average value of student achievement was 70.29 and learning completeness reached 94.11% or there were 32 students out of 34 students who had finished studying. These results indicate that in the first cycle classically students complete learning, because students who get scores > 70 are only 94.11% of the results, student learning completeness has been achieved because those who get scores > 70 are greater than 85% according to the desired percentage of completeness. This is because the students have repeated the teacher using learning using the STAD cooperative learning model. Based on this, it can be said that the cooperative learning model of the STAD model can have a very good impact on the activities of teachers, students and student learning outcomes of the Qur'an and Hadith in Class VII MTs Negeri 2 Kendari.